MARKETING STRATEGIES IN THE FACE OF PANDEMIC IMPACTS COVID-19 ON SUHERI CHIPS - Munawaroh, Nikmatul; Habiburrahman, Habiburrahman (Universitas Mercu Buana, 2022)
The results of the study on swot matrix combination formulation analysis (strenght, weakness, opportunity, and threat), Suheri Chip Aneka Rasa marketing strategy based on SO strategy that has the highest value of 5.54, WO strategy 2.80, ST strategy 3.29, WT strategy 0.55. Judging from the cartesius diagram of SWOT analysis, it is known that Suheri's efforts in The I Growth (SO Strategy), a very profitable position. Then the strategy that can be done can use the SO strategy (Strenght to take advantage of existing Opportunities) Is utilizing raw materials and improving the quality of products by using quality materials so that consumers can continue to be loyal to buy with large quantities, always maintain consumer confidence and increase the number of employees in order to increase the number of production, increase modern production tools in order to provide consumer orders with the amount demanded.